Análisis de la educomunicación en el desarrollo de actividades académicas virtuales con habitantes del Recinto Mina de Piedad, cantón Ventanas, año 2021 - Quinchuela Pendolema, Edgar Stalin (2021)
Nowadays the teaching in the campuses is permeated by involution in which a large number of people continue to use the traditional teaching model in the practice of educational processes in this way the acquired knowledge continues to be transmitted in the same way in the that they were learning. For this reason, the students and researchers of this project make the decision to propose an educommunicative strategy, in which, from the practice of new methodologies, the importance of re-evaluating educational scenarios can be evidenced to guarantee that students acquire the competences and the ideal knowledge to face the new dynamics of the labor and professional world. In the same way, to achieve that over time this work can be the basis for the development of a structured project that triggers the promotion or creation of an institutional instruction that helps to energize educational scenarios and strengthen the knowledge acquired and constantly search for new alternatives to teach.